Models of Inflation and the Costs of Disinflation - Meredith, Guy (IMF Working Papers; Working Paper ;, 1991)
This paper focuses on the output costs of disinflation. A model of inflation with both forward and backward elements seems to characterize reality. Such an inflation model is estimated using data for industrial countries, and the output costs of a disinflation path are calculated, first analytically in a simple theoretical model, then by simulation of a global, multi-region empirical model. The credibility of a preannounced path for money consistent with the lowest output loss is considered. An alternative, more credible policy may be to announce an exchange rate peg to a low inflation currency.